Industrial Revolution (IR) 4.0: it is essential in today's business / Abd Rasyid Ramli, Norhidayah Ali and Rosliza Md Zani - Ramli, Abd Rasyid; Ali, Norhidayah; Md Zani, Rosliza (Faculty of Business and Management, Universiti Teknologi MARA Cawangan Kedah, 2022)
Industry 4.0 (IR 4.0) has become a new buzzword for industrialists, academicians, engineers, scientists, and many other intellectuals in recent years. It has received a lot of attention worldwide. Cyber-Physical Systems, Big Data, the Internet of Things (IoT), 3D Printing, Autonomous Robots, Cloud Computing, Augmented Reality, and other major technology areas are among the main technological fields that will digitise the entire value chains in numerous industries. The benefits of implementing the IR4.0 technologies are predicted to be massive in terms of efficiency, flexibility, quality, and mass customisation. It is projected to bring improved product range and automation and boost customer satisfaction (Kumar & Kumar, 2020). The Fourth Industrial Revolution is divided into nine primary pillars; each considered a key component of Industry 4.0. These nine pillars describe how producers apply the latest technologies to improve every aspect of their production processes. Whether in the manufacturing area or not, it is critical to understand these pillars because they are projected to have a widespread impact across all industries and society. The IR 4.0 consists of nine pillars: Big Data and Analytics, The Internet of Things (IoT), Augmented Reality (AR), The Cloud, Autonomous Robots, Additive Manufacturing, Cyber Security, Horizontal and Vertical System Integration, and Simulation.